2023
DOI: 10.1093/molbev/msad042
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution is not Uniform Along Coding Sequences

Abstract: Amino acids evolve at different speeds within protein sequences, because their functional and structural roles are different. Notably, amino-acids located at the surface of proteins are known to evolve more rapidly than those in the core. In particular, amino-acids at the N- and C-termini of protein sequences are likely to be more exposed than those at the core of the folded protein due to their location in the peptidic chain, and they are known to be less structured. Because of these reasons, we would expect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…This also seemed to be the case for other substitution models (results not shown). This result is in agreement with Bricout et al [10] who also found this pattern in a large scale analysis of empirical alignments.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This also seemed to be the case for other substitution models (results not shown). This result is in agreement with Bricout et al [10] who also found this pattern in a large scale analysis of empirical alignments.…”
Section: Resultssupporting
confidence: 93%
“…We computed the number of stop codons in all genes in the database and at all three phases, and did not observe an excess of alignments with 0 or 1 stop codons per sequence (Supplementary Figure S17). Instead, it seems to correspond to the pattern found by Bricout et al [10]. However, in the future it will be interesting to investigate the realism of existing codon models, on a data set of coding DNA sequences.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, it's important to note that the reduced alignment coverage does not necessarily result in the detection of a lower number of PSS within the region. Apart from our finding, a study detected a similar trend of a faster evolutionary rate at the termini of a protein sequence even after removing poorly aligned regions [71]. This further enhances the presence of malleable regions at the termini of protein sequences to harbour evolutionarily innovative opportunities.…”
Section: Discussionsupporting
confidence: 80%
“…Values close to 1 correspond to cases where Y is strongly preferred in the fungi but not in the metazoa, and vice versa for negative values. We also stratify the data according to accessibility (buried, intermediate, exposed) given established relationships between residue exposure and the rate of evolution (Echave et al , 2016; Bricout et al , 2023), and that the molecular impact of phosphorylation will likely depend upon the accessibility of the phosphosite (Figure S5f). This analysis does not reveal any significant evidence for Y counter-selection for pYs relative to non-pYs ( Figure 5f, Table S14) .…”
Section: Resultsmentioning
confidence: 99%